2013
DOI: 10.1080/00140139.2013.837514
|View full text |Cite
|
Sign up to set email alerts
|

Association of job strain with working hours, shift-dependent perceived workload, sleepiness and recovery

Abstract: We explored the relationship of job strain with working hours, shift-dependent perceived workload, sleepiness and recovery. Nurses/nursing assistants (n = 95) were recruited from wards that belonged to either the top (high-strain group, HJS) or the bottom (low-strain group, LJS) job strain quartiles of a Job Content Questionnaire survey of employees in five health care districts and four cities in Finland. Three-week field measurements during naturally occurring shift schedules and a subset of pre-selected shi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 45 publications
4
34
1
3
Order By: Relevance
“…Our data obtained using an index of objective workload indicated the safe finding. Notably, overtime work is multifaceted-on one hand, it results in higher job stress 2) , while on the other hand, it increases levels of participation in decisionmaking and opportunities to develop special abilities 11) . The present results suggest the importance of perceived stressors of workers, such as recognizing one's method of handling occupational stress, that is to say, SOC, in determining whether overtime work is a benefit or a hindrance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data obtained using an index of objective workload indicated the safe finding. Notably, overtime work is multifaceted-on one hand, it results in higher job stress 2) , while on the other hand, it increases levels of participation in decisionmaking and opportunities to develop special abilities 11) . The present results suggest the importance of perceived stressors of workers, such as recognizing one's method of handling occupational stress, that is to say, SOC, in determining whether overtime work is a benefit or a hindrance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research suggests that overtime work is associated with considerable mental and physical stress 2) . Conversely, Hobson and Beach reported the importance of determining psychological health by perceived workload compared with actual workload 3) .…”
mentioning
confidence: 99%
“…However, in a study by Steptoe, Cropley, Griffith, and Kirschbaum (2000), HJS among teachers was associated with significantly elevated salivary cortisol on the morning of a work day compared to the teachers with LJS. In a previous study, we found job-strain group differences in perceived workload and intershift recovery (Karhula et al, 2013), but these differences were not manifested in the stress biomarkers. The findings on biomarkers and self-reported stress are inconsistent (Fujimaru et al, 2012;Fujiwara et al, 2004), while recovery and cortisol results are more concordant (Gustafsson, Lindfors, Aronsson, & Lundberg, 2008).…”
Section: Discussionmentioning
confidence: 66%
“…As described previously (Karhula et al, 2013), we formed the HJS and LJS groups by grouping the wards with at least five respondents on the JD and JC scales and using a median split to identify HJS (high demands and low control) and LJS (low demands and high control) wards. Using these cutoff points, we identified employees who belonged to the HJS or LJS group also on the basis of their individual mean JD and JC scores.…”
Section: Study Samplementioning
confidence: 99%
“…We recently studied the association of work stress with insomnia using both subjective and objective analysis of sleep (19,20). The shift-working women were recruited from hospital wards that belonged to either the top or bottom job strain quartiles of the Job Content Questionnaire.…”
mentioning
confidence: 99%